The quality of numerical modelling of the flow around two buildings with different heights - Błazik-Borowa, Ewa (Computer Assisted Methods in Engineering and Science, 2009)
The paper is devoted to the problems with quality of numerical modeling for two-dimensional incompressible flow around two models of buildings with different heights. The calculations have been made with use of the turbulence model k-ε in the standard version and with the Finite Volume Method. The quality evaluation for the calculation is based on the comparison of the results with measurements in a wind tunnel. Hence, in this paper there have been presented the graphs of averaged velocities which are results of author’s own measurements, as well as the graphs presenting the error in the calculated flow velocities. The main conclusion drawn from the research is that the flow around two models is more complicated than the flow around the single one and therefore the calculation results for the set of models are less accurate in comparison with the ones obtained for the single model.